PHYTOCHEMICAL COMPOSITION OF LIPOPHILIC FRACTION OF PLANTS OF THE PLANT ROSA CANINA L. GENUS ROSA - Y.S. Ikhsanov; G.E. Tasmagambetova; Y.A. Litvinenko; G.Sh. Burasheva; G.A.Seitimova (Academic Scientific Journal of Chemistry, 2020)
he genus of wild rose, or Rosa L., belongs to the family Rosaceae. It has many cultural forms, bred under the general name Rosa. At the moment, more than 400 species of rose hips are known. Usually these are upright shrubs, less often creepers, sometimes low tree-like forms or almost herbaceous plants. Rosehip is common in the temperate and subtropical zones of the Northern Hemisphere, it can often be found in the mountainous regions of the tropical zone. Some species of rose hips are common from the Arctic Circle in the north to Ethiopia in the south. On the American continent - from Canada to Mexico, Favorable conditions for Rosehip are in the Mediterranean region. Several species of the Rosehip genus have an extensive distribution area. Kazakhstan has significant resources of medicinal raw materials of plant origin. Among the most priority representatives of the wild flora are species of the rosehip genus - Rosa L. as a most valuable medicinal plant. In total, 21 species of wild rose grow in the republic, including 5 in the central Kazakhstan: R. glabrifolia - sh. naked, R. laxa Retz. - w. loose, R. acicularis Lindl. - (W. needlefish), R. majalis Herrm. (R. cinnamomea L.) - sh. May (W. cinnamon) and R. pimpinellifolia L. (R. spinosissima L.) - W. femoral cell. Kazakhstan species of the genus Rosa L. Rose hips are characterized by a high content of biologically active substances and are widely used both in medicine and in cooking. In this paper, a comparative analysis of rose hips, Rosa canina L., harvested in the fall of 2018 is carried out. Plant raw materials are collected in the southern region of the Republic of Kazakhstan (Almaty region). The crushed air-dry raw materials were extracted with hexane and chloroform in the ratio of raw materials-reagent (1:10) in a Soxhlet apparatus. The resulting extract was concentrated under mild conditions to a thick concentrate, which was analyzed on a gas chromatograph with a mass selective detector. The analyzes were carried out on a gas chromatograph with a mass spectrometric detector 6890N / 5973C (Agilent, USA). The peaks detected in the chromatograms were identified using the NIST’11 and Wiley 10 mass spectral libraries. The article first studied and conducted a comparative analysis of lipophilic substances contained in the fruits of the plant Rosa canina L, harvested in the Almaty region. The extracts mainly include hydrocarbons, derivatives of higher carboxylic acids, higher alcohols and some other substances, in particular butyl tetradecyl ether of hydrochloric acid, [4- (2-methylpentanoylsulfamoyl) phenyl] amide of 2-methylpentanoic acid in hexane extract and, butyl undecyl ether sulfuric acid, eicosyl trifluoroacetate and ethoxycarbonyl-3-methyl-4-azafluorenone, 2-fluorenilim in the chloroform extract. Further work will be continued in order to determine the potential biological activity of the obtained extracts